Poems and reflections on language and the theme of home - Van Wyk, Gene; Menezes de Souz, Lynn Mario T.; Jansen, Nicole K.; Braaf, A.; Cogill, Shannon (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Poems and reflections by various authors.